The past and present of Érmellék wine region - Kiss, Klára (Acta Agraria Debreceniensis, 2013)
Érmellék is an area of the Partium. It is situated between Szilágy and Bihar counties and between River Kraszna and Berettyó. Its name is from Ér, the small brook, which crosses the area. Érmellék is famous for its wine production, because its climate is favourable for this kind of trade. Only a few information sheets of the small Partium-belonging micro-region, Érmellék are published nowadays. Érmellék has extremely picturesque architectural wine cellar rows, of which ”szalacsi” wine cellar row (wine cellar row system) with its unique structure consists of about a thousand cellars.